IN SILICO PHARMACOKINETIC, BIOACTIVITY AND TOXICITY STUDY OF SOME SELECTED ANTI-ASTHMATIC AGENTS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Asthma is a disease affecting the airways that carry air to and from lungs. Exposure to various irritants and substances that trigger allergies (allergens) can trigger signs and symptoms of asthma. The prevalence of asthma varies widely in different regions of the world due to distinct genetic, environmental and occupational risk factors. In this research investigation, we study the pharmacokinetic, drug-likeness, bioactivity profile and toxicity profile of some selected anti-asthmatic agents by computational methods. The study provides the information about the pharmacokinetic and toxicity of existing drugs that can be used for design and development of new anti-asthmatic agents with more potency and lesser toxicity.